2011
DOI: 10.1155/2011/937843
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nuclear Hormone Receptors: PPARαAgonists as Potential Disease-Modifying Drugs for Rheumatoid Arthritis

Abstract: In recent years, peroxisome proliferator-activated receptors (PPARs) have received growing interest due to the broad spectrum of their biological activities. PPARα, an isoform of PPAR, plays an important role in lipid homeostasis and inflammation, which makes it a potential target for the treatment of chronic inflammatory disorders, including RA. This paper reviews studies on the properties of PPARα agonists which may be pertinent to the treatment of RA. These properties include effects on lipid metabolism, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…In RA, a major source of M1 cytokines (TNF-α, IL-1β, IL-12p70) (50) in the joints are the synovial macrophages, whose number correlate with the inflammatory disease activity (51). On this basis, PPARδ and PPARγ are considered potential disease-modifying drugs for RA (52,53). In a murine model of experimental colitis, recruitment of CCL11-expressing Ly6C hi CCR2 + inflammatory monocytes into the colon correlates with eosinophil infiltration and histopathology (54).…”
Section: Pathologymentioning
confidence: 99%
“…In RA, a major source of M1 cytokines (TNF-α, IL-1β, IL-12p70) (50) in the joints are the synovial macrophages, whose number correlate with the inflammatory disease activity (51). On this basis, PPARδ and PPARγ are considered potential disease-modifying drugs for RA (52,53). In a murine model of experimental colitis, recruitment of CCL11-expressing Ly6C hi CCR2 + inflammatory monocytes into the colon correlates with eosinophil infiltration and histopathology (54).…”
Section: Pathologymentioning
confidence: 99%
“…PPARα can be activated by endogenous ligands (fatty acids) and pharmacological agents (such fibrates) (Table 1) [10]. Experimental studies [15][16][17] have shown that the degradation by oxidation of proinflammatory molecules such as LTB4 (ligand of PPARα) or arachidonic acid is enhanced after PPARα stimulation. In animal models, in gene-modified mice PPARα -/-, it was detected a prolonged inflammatory response and these data are related to lack of degradations of chemotactic inflammatory eicosanoids LTB4 [16,17].…”
Section: Ppar Alpha In Chronic Inflammations and Diseasesmentioning
confidence: 99%
“…Experimental studies [15][16][17] have shown that the degradation by oxidation of proinflammatory molecules such as LTB4 (ligand of PPARα) or arachidonic acid is enhanced after PPARα stimulation. In animal models, in gene-modified mice PPARα -/-, it was detected a prolonged inflammatory response and these data are related to lack of degradations of chemotactic inflammatory eicosanoids LTB4 [16,17]. Furthermore, in wild-type mice, but not in PPARα -/mice, treatment with WY-14643, a ligand of PPARα, suppressed a number of acute phase genes such as fibrinogen, serum amyloid Pcomponent, lipocalin 2, serum amyloid A-2, metallothioneins [15,17].…”
Section: Ppar Alpha In Chronic Inflammations and Diseasesmentioning
confidence: 99%
See 2 more Smart Citations